Canoes lined up on the shore of the Summer Tent island, Isle of Pines, Knife Lake, Boundary Waters Canoe Area, Minnesota - Dorothy Molter Museum (Dorothy Molter Museum, 1970)
Canoes lined up on the shore of the Summer Tent island as approached from the foot bridge leading from the Cady Cabin island.